Assistance in Financial Administration Management and Student Affairs at Madrasah Diniyah - Wahyudin, Aji; Akbar, Fadhil; Saifuddin, Muhammad; Maulana, Agung; Fadlil, Ahmad (Al-Qalam Institute, 2025)
This community service research aims to improve the management of financial administration and Santrian at Madrasah Diniyah. This research focuses on implementing a more structured and transparent system to improve financial accountability and the organization of student activities. The method used in this study is Participatory Action Research (PAR), which involves the active participation of madrasah managers and staff in the training and implementation process. The results of the study show that there has been a significant improvement in financial management, with the implementation of a more transparent and efficient digital financial recording system. In addition, the management of student activities becomes more organized with a clear schedule and systematic evaluation. However, challenges related to limited resources are still a major obstacle in sustaining these improvements. The study concludes that ongoing support and resource development are indispensable for long-term success. Further research may explore the application of this practice in other educational institutions in rural areas.